School-Based Agricultural Education Industry Certifications: Part 1—Introduction to Industry Certifications - Devon E. Morrison; Debra M. Barry; Carla B. Jagger (EDIS)
"Introduction to Industry Certifications" briefly discusses the history of agricultural education and the Smith-Hughes Act. It also provides an explanation as to what industry certifications are, as well as recognizes the organizations and the different types of certifications available to students within the Agriculture and Natural Resources pathway.